Mucormycosis: A clinical-pathological case series study (Research, Society and Development, 2024)
The aim of this study was to provide an overview of the possible presentations or forms of this rare, invasive fungal infection of the face, comparing it from diagnosis to treatment. This is an observational, descriptive, case series study, in which all cases diagnosed with fungal infections on the face were reviewed from the files of the Hospital Estadual de Urgências Governador Otávio Lage de Siqueira, Goiânia, GO, Brazil. Clinical data were obtained from patient records and radiographic characteristics were evaluated in each case. All cases were reviewed microscopically to confirm the diagnosis. Three cases of patients with mucormycosis fungal infection were identified, 1 in a woman and 2 in men. Both with common clinical manifestations: amaurosis, maxillary sinusitis, facial nerve involvement and extensive necrosis of the involved region. The diagnostic elucidation of the cases was carried out through microbiological examinations and computed tomography. They were conducted using a multimodal approach, including control of underlying predisposing factors, early administration of active antifungal agents at optimal doses, and complete removal of any infected tissue. In conclusion, mucormycosis infections are rare, invasive and usually fatal, with a low survival rate. It is commonly disseminated in patients with compromised immunity, particularly those with decompensated diabetes. There is still a lack of literature on the definitive management of this disease involving the stomatognathic system. This article emphasizes the need for correction of the underlying predisposing factor and early diagnosis with an aggressive multimodal treatment approach to provide the best chance of survival.